El rostro familiar de los nuevos global players: la gran empresa familiar en México, Brasil y China en el siglo XXI - Fernández Pérez, Paloma (2011)
Giant firms from emerging economies are increasingly becoming global players. Few studies have seriously analyzed, however, the high level of family control in these giant firms, and its economic significance. The present article has elaborated a pioneering data base with the largest family firms in Mexico, Brazil and China, and has identified who are the families who control them, and argues that their weight and influences are more important than usually acknowledged.